EXPERIMENTAL PROGRAM FOR THE FORMATION OF THE VALUE AND SENSE PICTURE OF THE JUNIOR SCHOOLCHILD (Pedagogy of Higher and Secondary Education, 2022)
Article demonstrated of the problem of education children in the inplementation of educational work. Consideres the differents tecitions in relach to thr interpretation of the term development children. Definet program and methods of pedagogic development children.
Keywords: legal education; expedient; pinches pies; define knowledge